Optimal Inflation Rate for Nepal - Timsina, Neelam; Panta, Rajan Karishna; Dangal, Madhav; Chaulagain, Mahesh (NRB Economic Review, 2017)
This paper estimates the optimal inflation rate in Nepal based on the data of the period 1978–2016. The novelty of the analysis is that it probes possible nonlinearity of the hypothesized impact of inflation on economic growth using alternative specifications. The results suggest that there exists a threshold effect of inflation. The Ordinary Least Squares method estimates the turning point of inflation to be 6.25 percent while that of the Hansen (2000) method shows the threshold level to be 6.40 percent. The maximum impact on growth associated with the turning point, and at the mean levels of other explanatory variables is quite high at 4.59 percent. The results suggest that Nepal should adopt an inflation target range around the computed optimal inflation rate to lower the inflation expectation and enhance economic growth.